Rapid Synthesis: Examining the Impact of Drop-in Centres - Wilson, MG (My University, 2015)
An assessment of what is known about the impact of drop-in centres. The rapid synthesis was conducted to address a question posed by a health system policymaker or stakeholder to the McMaster Health Forum’s Rapid Response program.
Keywords: impact; drop-in; centres